Iron Catalysis in Target Synthesis - DaBell, Peter; Thomas, Stephen P. (Synthesis, 2020)
The use of iron-catalysed organic transformations in the total syntheses of natural products has increased significantly. Iron-catalysed cross-coupling reactions are now widely applied in total syntheses and many other transformations, such as alkene functionalisation, oxidation, and cyclisation. The development of these processes, as well as many examples of their use in target synthesis, is presented here.1 Introduction2 Cross-Coupling Reactions3 Functionalisation of Unactivated Alkenes4 Carbocyclisation Reactions5 Oxidations6 Further Examples7 Conclusions
Keywords: alkene functionalisation; carbocyclisation; cross-coupling; drug molecule synthesis; iron catalysis; natural product synthesis; oxidation; transition metal catalysis